KONSEP BELAJAR MENURUT KI HADJAR DEWANTARA DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Wawan Eko Mujito (Jurnal Pendidikan Agama Islam, 2014)
Ki Hajar Dewantara an educational leaders in Indonesia. Ki Hajar Dewantara have learned concepts that are conservative and make the learner as central to the learning process. Based on this background, it is necessary to learn Ki Hajar Dewantara formulation appropriate to the context of Islamic Education.The purpose of this study is to explore the concept of learning by Ki Hajar Dewantara and express their relevance to Islamic education.This study is a literature research. Material object of this research is to learn the result of thinking Ki Hajar Dewantara. The approach used is a psychological approach. This is a qualitative study, using the document as a source of research and power analysis method is content analysis.The study found that learning by Ki Hajar Dewantara is a liberating learning learners. Liberate means that learners are developed in accordance with the talent and interest is based on the existing potential that idea, feeling, and intention. The development is expected to transform into a human learners can master yourself, independent, without having to depend on others. The role of educators is to guide, direct, and motivate learners with basic affection. Learners is central to learning activities are carried out. The method used in the learning process should be based on compassion. It was also found that the study in view of Ki Hajar Dewantara relevant to Islamic education. It can be seen from the concept study developed by Ki Hajar Dewantara not contrary to Islamic education. Only the term he uses a different but similar meaning.